Answers

The Brainliest Answer!
2014-06-27T21:03:56+05:30
Given,P(x) = 5x-4x²+3
            P(0) = 5(0) - 4(0)² + 3
                    = 0 - 4(0) + 3
                    = 0 - 0 + 3
                    = 3
Therefore ,the polynomial 5x-4x²+3 = 3 ,when x = 0

3 4 3
2014-06-27T21:09:23+05:30
Put x =0 in the equation 5x-4x square +3
  5(0)- 4(0)square +3
=0-0+3
=3
1 3 1
i hope it will help u.
plz mark as best!!!!!!!!!!!
thnx........ive aaaalready gott a clear answr.............
ok
f(x)=3
bcoz f(x)=0-0+3
than f(x)=3